Microfeed incorporated with probiotic for aquaculture: a review - Yaslikan, Nor Mala; Yaminudin, Jasmin; Rasdi, Nadiah Wan; Karim, Murni (Scienceline Publication, 2023)
Ensuring the availability of high-quality larvae in sufficient quantities remains a significant bottleneck for the grow-out phase of aquaculture. Over the past century, various alternative dietary solutions for larval stages have been explored, encompassing bacteria, microalgal pastes, yeasts, and various inert microparticles, though with inconsistent outcomes. This review aimed to discuss the innovative integration of probiotics into microfeeds, highlighting encapsulation, coating, and fermentation techniques to propel aquaculture productivity. Microfeeds, which are often nutrient-rich and easily assimilated in powdered or liquid form, play a crucial role in larval fish nutrition. These can be classified into microencapsulated, dry, liquid, and live feeds. The choice of microfeed is pivotal, ensuring appeal, digestibility, and water stability tailored to each larval stage. As probiotics gain popularity in aquaculture for their potential to enhance growth, bolster disease resistance, and improve water quality, their administration methods have diversified. The probiotics can be administered through direct immersion and bath treatments to biofloc systems and feed additives. The results indicated that microfeed incorporated with probiotics showed a positive result impact on the aquaculture industry